Risk management system - Nedbailo, А. (Ways to Improve Construction Efficiency, 2018)
The article deals with the risk management strategy of the Bank and observes the principle of break-even activity, aimed at ensuring the optimal balance between the profitability of individual business areas and the level of risk assumed by the Bank in carrying out certain operations.